Doping effect of l-cystine on structural, UV–visible, SHG efficiency, third order nonlinear optical, laser damage threshold and surface properties of cadmium thiourea acetate single crystal. (January 2017) - Azhar, S.M.; Anis, Mohd; Hussaini, S.S.; Kalainathan, S.; Shirsat, M.D.; Rabbani, G.
Abstract: The present article is focused to investigate the influence ofl -cystine (LC) on linear-non-linear optical and laser damage threshold of cadmium thiourea acetate (CTA) crystal. The structural parameters of pure and LC doped CTA crystals have been determined using the single crystal X-ray diffraction technique. The functional groups of grown crystals have been identified by means of fourier transform infrared (FT-IR) analysis. The UV–visible spectral analysis has been done in the range of 200–900 nm to ascertain the uplifting influence of LC on optical properties of CTA crystal. The second harmonic generation (SHG) efficiency of LC doped CTA crystal is found to be higher than CTA and KDP crystal. The Z-scan technique has been employed to determine the third order nonlinear optical (TONLO) nature of LC doped CTA crystal at 632.8 nm. The self focusing tendency confirmed the strong kerr lensing ability of LC doped CTA crystal. The TONLO susceptibility (χ 3 ), refraction (n2 ) and absorption coefficient (β) has been calculated using the Z-scan data. The laser damage threshold of pure and LC doped CTA crystals has been measured using the Q-switched Nd:YAG laser and its is found to be in range of GW/cm 2 . The surface analysis has been done by means of etching studies. Graphical abstract: Highlights: LC improved optical transparency and optical constants of CTA crystal. Enhanced SHG efficiency of LC-CTA crystal is 1.68(KDP) and 1.35(CTA). The LC-CTA crystal with χ 3 of 6.18×10 −5  esu possess strong kerr lensing effect. Multiphoton absorption facilitated reverse saturable absorption was observed in LC-CTA crystal. Laser damage threshold of CTA and LC-CTA crystal is in range of GW/cm 2.